The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4103/0970-0358.191320
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tools in maxillofacial fractures: Is there really a need of three-dimensional computed tomography?

Abstract: Introduction:Because of its functional and cosmetic importance, facial injuries, especially bony fractures are clinically very significant. Missed and maltreated fractures might result in malocclusion and disfigurement of the face, thus making accurate diagnosis of the fracture very essential. In earlier times, conventional radiography along with clinical examination played a major role in diagnosis of maxillofacial fractures. However, it was noted that the overlapping nature of bones and the inability to visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…After comparing conventional 2D radiographs with CT scans, Shah et al 26 reported that CT scan considerably increased the surgeon's ability to diagnose ZMC, zygomatic arch, and inferior orbital floor fractures. The CT scan seems to be a precise method for the detection of fracture, soft tissue involvement, and ocular position.…”
Section: E7mentioning
confidence: 99%
See 1 more Smart Citation
“…After comparing conventional 2D radiographs with CT scans, Shah et al 26 reported that CT scan considerably increased the surgeon's ability to diagnose ZMC, zygomatic arch, and inferior orbital floor fractures. The CT scan seems to be a precise method for the detection of fracture, soft tissue involvement, and ocular position.…”
Section: E7mentioning
confidence: 99%
“…The CT scan seems to be a precise method for the detection of fracture, soft tissue involvement, and ocular position. 7,26 In the present study, 3D reconstruction and volume measurements were performed with the aid of Mimics software. This biomedical engineering software can be used for 3D reconstruction and anthropometric analysis.…”
Section: E7mentioning
confidence: 99%
“…According to these authors, visualization in three dimensions helps the complex process in which the surgeon visualizes operational planning 4 . This advantage is also pointed out in the clinical trial by Shah et al 11 . Perandini, et al 12 who reinforce in their articles the importance of 3D-CT in the diagnosis of relatively common conditions such as thrombosis, stenosis of the airways, exophytic cancer and trauma.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, fractures involving the maxillary sinus are frequently accurately identified. Shah et al (6) investigated the efficacy of three-dimensional computed tomography in the diagnosis of maxillofacial fractures. They compared their study findings with those of Baek et al (11) and attributed the resulting discrepancies in the determination of undisplaced fractures to slice thickness (6).…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al (6) investigated the efficacy of three-dimensional computed tomography in the diagnosis of maxillofacial fractures. They compared their study findings with those of Baek et al (11) and attributed the resulting discrepancies in the determination of undisplaced fractures to slice thickness (6). We were unable to identify seven of the maxillary fractures, though inside the cranial CT imaging field, these were undisplaced in character.…”
Section: Discussionmentioning
confidence: 99%